2015
DOI: 10.1038/nm.3860
|View full text |Cite
|
Sign up to set email alerts
|

Common clonal origin of central and resident memory T cells following skin immunization

Abstract: Central memory T (TCM) cells in lymph nodes (LN) and resident memory T (TRM) cells in peripheral tissues play distinct roles in protective immunity1-5. Both are generated after primary infections, but the clonal origin of TRM and TCM cells is unclear. To address this question, mice were immunized through the skin with either a protein antigen, a chemical hapten, or a non-replicating poxvirus. We then analyzed antigen activated T cells from different tissues using high-throughput sequencing (HTS) of the gene (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
252
1
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 248 publications
(275 citation statements)
references
References 25 publications
16
252
1
2
Order By: Relevance
“…This delay suggests that pathogenic lymphocytes need to return to the circulation, enter the skin, and become activated to trigger the formation of new plaques. These observations also support the notion that a continuous recruitment of T cells from lymphoid organs rather than a persistent activation of a priori skin-resident T cells is required to induce and maintain disease activity in psoriasis [Diluvio et al 2006;Gaide et al 2015].…”
Section: Efficacy In Psoriasissupporting
confidence: 79%
“…This delay suggests that pathogenic lymphocytes need to return to the circulation, enter the skin, and become activated to trigger the formation of new plaques. These observations also support the notion that a continuous recruitment of T cells from lymphoid organs rather than a persistent activation of a priori skin-resident T cells is required to induce and maintain disease activity in psoriasis [Diluvio et al 2006;Gaide et al 2015].…”
Section: Efficacy In Psoriasissupporting
confidence: 79%
“…It should be noted that T RM cells also show some level of disseminated lodgement, especially after repeated Ag exposure (31). But biases still remain, as demonstrated by Gaide et al (32), who showed enhanced challenge responses at regions of skin subjected to repeated contact sensitization, mirroring the observations of increased immunity in skin having cleared prior infection (24,31).…”
Section: Tissue-resident Memory T Cells and Fixed Immune Surveillancementioning
confidence: 92%
“…+ T RM cells develop from common memory cell precursors (27,32) that are present early postinfection and then quickly disappear from the circulation (25). Circulating memory cell precursors can be identified by their expression of the a-chain of IL-7R and their lack of expression of the differentiation marker KLRG-1 (66)(67)(68).…”
Section: Cd8mentioning
confidence: 99%
“…T RM cells are generated by immune challenges in peripheral tissues, provide rapid responses to rechallenge, and persist in the absence of antigen (12). Studies using mouse infection models have demonstrated that immune challenges in skin, whether they are infectious or hapten driven, lead to colonization of the entire skin surface with antigen-specific T RM (13,14). These cells are present in the highest numbers at the site of primary infection and at sites of subsequent rechallenge, are long lived, and are capable of rapid reactivation when specific antigen is reencountered.…”
Section: Putative Pathogenic T Cell Clones Utilize a Skewed Tcr Vα Rementioning
confidence: 99%